2020
DOI: 10.48550/arxiv.2005.00585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Robustness via Risk Averse Distributional Reinforcement Learning

Abstract: One major obstacle that precludes the success of reinforcement learning in real-world applications is the lack of robustness, either to model uncertainties or external disturbances, of the trained policies. Robustness is critical when the policies are trained in simulations instead of real world environment. In this work, we propose a risk-aware algorithm to learn robust policies in order to bridge the gap between simulation training and real-world implementation. Our algorithm is based on recently discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Learning robust and high-performance policies for continuous state-action reinforcement learning (RL) domains is crucial to enable the successful adoption of deep RL in robotics, autonomy, and control problems. However, recent works have demonstrated that deep RL algorithms are vulnerable either to model uncertainties or external disturbances [9,16,11,3,20,17,18,8]. Particularly, model uncertainties normally occur in a noisy reinforcement learning environment where the agent often encounters systematic or stochastic measurement errors on state observations, such as the inexact locations and velocity obtained from the equipped sensors of a robot.…”
Section: Introductionmentioning
confidence: 99%
“…Learning robust and high-performance policies for continuous state-action reinforcement learning (RL) domains is crucial to enable the successful adoption of deep RL in robotics, autonomy, and control problems. However, recent works have demonstrated that deep RL algorithms are vulnerable either to model uncertainties or external disturbances [9,16,11,3,20,17,18,8]. Particularly, model uncertainties normally occur in a noisy reinforcement learning environment where the agent often encounters systematic or stochastic measurement errors on state observations, such as the inexact locations and velocity obtained from the equipped sensors of a robot.…”
Section: Introductionmentioning
confidence: 99%